Comparative metabarcoding and biodiversity of gut-associated fungal assemblages of Dendroctonus species (Curculionidae: Scolytinae) - Pineda-Mendoza, Rosa María; Gutiérrez-Ávila, Jorge Luis; Salazar, Kevin F.; Rivera-Orduña, Flor N.; Davis, Thomas S.; Zúñiga, Gerardo (Frontiers in Microbiology, 2024)
The genus Dendroctonus is a Holarctic taxon composed of 21 nominal species; some of these species are well known in the world as disturbance agents of forest ecosystems. Under the bark of the host tree, these insects are involved in complex and dynamic associations with phoretic ectosymbiotic and endosymbiotic communities. Unlike filamentous fungi and bacteria, the ecological role of yeasts in the bark beetle holobiont is poorly understood, though yeasts were the first group to be recorded as microbial symbionts of these beetles. Our aim was characterize and compare the gut fungal assemblages associated to 14 species of Dendroctonus using the internal transcribed spacer 2 (ITS2) region. A total of 615,542 sequences were recovered yielding 248 fungal amplicon sequence variants (ASVs). The fungal diversity was represented by 4 phyla, 16 classes, 34 orders, 54 families, and 71 genera with different relative abundances among Dendroctonus species. The α-diversity consisted of 32 genera of yeasts and 39 genera of filamentous fungi. An analysis of β-diversity indicated differences in the composition of the gut fungal assemblages among bark beetle species, with differences in species and phylogenetic diversity. A common core mycobiome was recognized at the genus level, integrated mainly by Candida present in all bark beetles, Nakazawaea, Cladosporium, Ogataea, and Yamadazyma. The bipartite networks confirmed that these fungal genera showed a strong association between beetle species and dominant fungi, which are key to maintaining the structure and stability of the fungal community. The functional variation in the trophic structure was identified among libraries and species, with pathotroph-saprotroph-symbiotroph represented at the highest frequency, followed by saprotroph-symbiotroph, and saprotroph only. The overall network suggested that yeast and fungal ASVs in the gut of these beetles showed positive and negative associations among them. This study outlines a mycobiome associated with Dendroctonus nutrition and provides a starting point for future in vitro and omics approaches addressing potential ecological functions and interactions among fungal assemblages and beetle hosts.